2016
DOI: 10.1002/cae.21778
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of offshore engineering design skills on naval architecture master courses through potential flow CFD tools

Abstract: This paper presents a teaching-learning methodology focused on the acquisition of basic design principles in offshore engineering for a course entitled Projects in Offshore Maritime Structures, in a Master of Naval Architecture and Ocean Engineering. A new teaching procedure (including the Project-Based Learning approach), is proposed, for ensuring that students acquire skills related to the ability of analyzing and designing ocean structures. The roles of the Information and Communication Technologies, Comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Por un lado, ofrece a los estudiantes la posibilidad de aprender una herramienta específica que se utiliza en la industria de motores de aviación. También ayuda a involucrar a los estudiantes, ya que sienten que el esfuerzo que invierten en aprender la herramienta puede ser útil no solo para la asignatura sino también para sus futuras carreras profesionales (Gutiérrez-Romero, 2017). Por otro lado, desde una perspectiva puramente académica, permite al alumno disponer de una gran cantidad de cálculos de parámetros de ciclo con un esfuerzo reducido.…”
Section: Introductionunclassified
“…Por un lado, ofrece a los estudiantes la posibilidad de aprender una herramienta específica que se utiliza en la industria de motores de aviación. También ayuda a involucrar a los estudiantes, ya que sienten que el esfuerzo que invierten en aprender la herramienta puede ser útil no solo para la asignatura sino también para sus futuras carreras profesionales (Gutiérrez-Romero, 2017). Por otro lado, desde una perspectiva puramente académica, permite al alumno disponer de una gran cantidad de cálculos de parámetros de ciclo con un esfuerzo reducido.…”
Section: Introductionunclassified
“…On the one hand, it offers the students the possibility to learn a specific tool that is actually used in the aircraft engine industry. It also helps to engage the students since they feel that the effort they put into learning the tool can be useful not only for the subject but also for their future professional careers [14]. On the other hand, from a purely academic perspective, it allows the students to have available a great amount of cycle and performance parameters calculations with a reduced effort.…”
Section: Introductionmentioning
confidence: 99%
“…Regueiro et al [19] showed that the students appreciated computer-aided learning due to its "learning-by-doing" capabilities. Gutiérrez-Romero et al [10] stated that such experiences are perceived by the students as "closer to industry" compared to traditional work in the classroom. Burke et al [4] also provided evidence that modeling tools can help the students to gain a more deep understanding of complex phenomena and interactions (in their case, engine calibration), with particular advantages for foreign students.…”
Section: Introductionmentioning
confidence: 99%